The Recruitment Niche Predicts Plant Community Assembly Across a Hydrological Gradient Along Plowed and Undisturbed Transects in a Former Agricultural Wetland - Valdez, Jose W.; Hartig, Florian; Fennel, Sabine; Poschlod, Peter (Frontiers in Plant Science, 2019)
Seedling emergence in plant communities depends on the composition in the soil seed bank, in combination with species-specific responses to the environment. It is generally assumed that this juvenile transition, known as the recruitment niche, is a crucial filter that determines species’ distributions and plant community assemblies. The relative importance of this filter, however, has been widely debated. Empirical descriptions of the recruitment niche are scarce, as most field studies focus on environmental effects at later life stages. In this study, we examine the importance of the recruitment niche for predicting plant communities across a hydrological gradient in a disturbed and undisturbed area in Lake Schmiechen, Baden-Württemberg, Germany. We combine a seed bank experiment, measuring germination in a greenhouse under standardized conditions and different water levels, with field observations of plant communities along a hydrological gradient in ploughed and undisturbed transects in a former agricultural wetland. We find that hydrology consistently predicted plant community composition in both the germination experiment and in the field. The hydrological recruitment niches measured in the seed bank experiment correlated with the hydrological niche in both the ploughed and undisturbed area, with slightly stronger correlation in the ploughed area. We explain the latter by the fact that the seed bank experiment most closely resembling the ploughed area, whereas succession and competitive interactions become more important in the undisturbed area. Our results support the view that the recruitment niche is an important driver of species composition, in both the ploughed and undisturbed area. Recognizing the recruitment niche and the response of seeds within a seed bank to environmental gradients and anthropogenic disturbance is necessary to understand and predict future plant community composition.